2020
DOI: 10.1016/j.bpj.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Imaging of Adsorbed Pulmonary Surfactant Films

Abstract: Pulmonary surfactant (PS) is a lipid-protein complex that adsorbs to the air-water surface of the lung as a thin film. Previous studies have suggested that the adsorbed PS film is composed of an interfacial monolayer, plus a functionally attached vesicular complex, called the surface-associated surfactant reservoir. However, direct visualization of the lateral structure and morphology of adsorbed PS films using atomic force microscopy (AFM) has been proven to be technically challenging. To date, all AFM studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 51 publications
(82 reference statements)
3
49
0
Order By: Relevance
“…A sensor plate measures the variation in surface pressure over compression to yield surface pressure – area isotherms. It should be noted that in addition to the traditional Langmuir trough, the Langmuir-Blodgett technique has been adapted in the constrained drop surfactometer to study adsorbed surfactant films ( Xu et al, 2020 ). The comparison of such isotherms in the presence or absence of the test substance gives insights in the interaction of a substance with lung surfactant at the molecular level.…”
Section: Technical Details and Methodologiesmentioning
confidence: 99%
“…A sensor plate measures the variation in surface pressure over compression to yield surface pressure – area isotherms. It should be noted that in addition to the traditional Langmuir trough, the Langmuir-Blodgett technique has been adapted in the constrained drop surfactometer to study adsorbed surfactant films ( Xu et al, 2020 ). The comparison of such isotherms in the presence or absence of the test substance gives insights in the interaction of a substance with lung surfactant at the molecular level.…”
Section: Technical Details and Methodologiesmentioning
confidence: 99%
“…Apart from the parametric investigation of the effect of varying H 0 , to be undertaken next, the values H = 0.3 μm and H 0 = 0.14 μm are kept constant for the rest of the study. The validity of the selected value of H 0 is further supported in § 5, by discussing and interpreting additional experimental evidence (Xu et al 2020).…”
Section: Equilibrium Film Thickness At the Rim And The Onset Of Shear...mentioning
confidence: 77%
“…. Term H 0 is a key parameter for the problem, and its magnitude will be estimated from direct experimental evidence (Bastacky et al 1995;Xu et al 2020).…”
Section: The Final Equations and The Equilibrium Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence contradicts that prediction (64-67). 2) Multilamellar films: Several groups have shown that surfactant films on modestly curved surfaces collapse slowly when the subphase contains surfactant vesicles (64)(65)(66)(67). Electron micrographs show that at least portions of the alveolar film are multilamellar rather than monomolecular (68,69).…”
Section: Stability Of the Interfacial Filmmentioning
confidence: 99%